Cerebrospinal fluid and plasma metabolomics of acute endurance exercise. Issue 7 (17th June 2022) - Li, Kefeng; Schön, Martin; Naviaux, Jane C.; Monk, Jonathan M.; Alchus‐Laiferová, Nikoleta; Wang, Lin; Straka, Igor; Matejička, Peter; Valkovič, Peter; Ukropec, Jozef; Tarnopolsky, Mark A.; Naviaux, Robert K.; et al.
Abstract: Metabolomics has emerged as a powerful new tool in precision medicine. No studies have yet been published on the metabolomic changes in cerebrospinal fluid (CSF) produced by acute endurance exercise. CSF and plasma were collected from 19 young active adults (13 males and 6 females) before and 60 min after a 90‐min monitored outdoor run. The median age, BMI, and VO2 max of subjects was 25 years (IQR 22–31), 23.2 kg/m 2 (IQR 21.7–24.5), and 47 ml/kg/min (IQR 38–51), respectively. Targeted, broad‐spectrum metabolomics was performed by liquid chromatography, tandem mass spectrometry (LC–MS/MS). In the CSF, purines and pyrimidines accounted for 32% of the metabolic impact after acute endurance exercise. Branch chain amino acids, amino acid neurotransmitters, fatty acid oxidation, phospholipids, and Krebs cycle metabolites traceable to mitochondrial function accounted for another 52% of the changes. A narrow but important channel of metabolic communication was identified between the brain and body by correlation network analysis. By comparing these results to previous work in experimental animal models, we found that over 80% of the changes in the CSF correlated with a cascade of mitochondrial and metabolic changes produced by ATP signaling. ATP is released as a co‐neurotransmitter and neuromodulator at every synapse studied to date. By regulating brain mitochondrial function, ATP release was identified as an early step in the kinetic cascade of layered benefits produced by endurance exercise.